The Rewarding Effect of Pictures with Positive Emotional Connotation upon Perception and Processing of Pleasant Odors—An FMRI Study - Hummel, Thomas; Fark, Therese; Baum, Daniel; Warr, Jonathan; Hummel, Cornelia B.; Schriever, Valentin A. (Frontiers in Neuroanatomy, 2017)
This fMRI study was designed to investigate the effect of cross-modal conditioning in 28 female volunteers. Subjects underwent initial fMRI block design scanning during which three pleasant olfactory stimuli were presented and had to be rated with respect to intensity and pleasantness. This was followed by an odor identification task spread out over 3 days: the experimental group was rewarded for successful trials (correct odor identification) with emotionally salient photos, whilst the control group only received randomly displayed, emotionally neutral, pictures. In the final scanning session, the odors were again presented, and subjects rated pleasantness and intensity. Both pleasantness ratings and fMRI data showed effects of the rewarding procedure. Activation in nucleus accumbens and the orbitofrontal cortex confirmed the hypothesis that learnt association of odors with visual stimuli of emotionally positive valence not only increases pleasantness of the olfactory stimuli but is also reflected in the activation of brain structures relevant for hedonic and reward processing. To our knowledge, this is the first paper to report successful cross-modal conditioning of olfactory stimuli with visual clues.